Mother-Daughter Relationship in the Plays Tara and Thirty Days in September of Mahesh Dattani - Bhattacharya, Suchismita; Suresh, P. (International Journal of Engineering and Technology, 2018)
The mother-daughter relationship is the most beautiful and innocent relationship in this world. A mother does every possible thing to make her child happy. The relationship between a mother and daughter has considered one of the sweetest relationships on the planet because a daughter reflects the character and nature of her mother. In most of the cases, daughter is just the carbon copy of her mother. A child rests well in the mother's lap because it is the safest abode for the child. A child, especially a girl child is always special to her mother and vice-versa, but the feeling of being an individual gets ruined when a relationship between a mother and her daughter loses the balance. Relationships are based on trust, belief and love, and these three aspects are essential for the survival of any healthy relationship. Connections can either be made or can be broken, based on these three elements. The plays Tara and Thirty Days in September, written by the dramatist Mahesh Dattani, talk about the relationship between a mother and a daughter and the games also deal with the psychological mindset of the mother(s) and the daughter(s) and their sufferings in the urban society of India.Â